Disturbance Effect of Pipe Jacking Group Adjacent Excavation on Surrounding Soil - Changbai Wang; Jimin Liu; Hua Cheng; Haibing Cai (Advances in Civil Engineering)
Under the modern and complicated urban environment, clarifying the interaction mechanism and mutual influence mechanism between the urban tunnel and the surrounding environment is of considerable significance to the construction and operation of the tunnel. To understand and grasp the excavation-induced disturbance range and mechanism of adjacent pipeline jacking group on surrounding soils, this paper carries out relevant researches. Based on a case history of a three-hole parallel adjacent jacking pipeline in shallow overburden, a field test and assessment are performed. By setting monitoring points around the monitoring section, the earth pressure and water pressure under different buried depths and different spacing are monitored. For further discussion, the general law of soil disturbance around single-hole, double-hole, and three-hole jacking is investigated, the calculation method of lateral disturbance range and overlapping area range of pipe jacking group is deduced, and the degree of soil disturbance is evaluated as well. The results show that there will be different degrees of disturbance superposition in parallel multihole jacking due to the influence of the spacing, and the disturbance intensity is greatly affected by the parallel distance and buried depth.